Mechanical properties and dimensional stability of particleboard fabricated from steam pre-treated banana trunk waste particles - Wan Nadhari, Wan Noor Aidawati; Danish, Mohammed; Mohd Nasir, Muhammad Syafiq Ridhwan; Boon, Jia Geng (Elsevier, 2019)
This study investigated the mechanical strength and dimensional stability of steam pre-treated banana trunk waste trunck waste binderless (free from synthetic adhesive) particleboards. The dried banana trunk wastes particles were subjected to steam pre-treatment for 15 min at chosen temperatures of 111 °C, 121 °C, and 131 °C, respectively. The targeted density of the particle board was fixed around 0.7 g/cm3, to achieve this density of binderless particleboard the steamed banana particles were hot pressed at a temperature of 180 °C for 40 min. The obtained particleboard was tested for standard mechanical and physicochemical properties. The test results indicated that banana trunk waste particle after steam treated at 121 °C temperature resulting particleboard was having optimum modulus of rupture (MOR, 4.57 MPa) and modulus of elasticity (MOE, 662.33 MPa) compared to without steam treated banana trunk waste binderless particleboard (MOR, 1.54 MPa; MOE, 296.74 MPa) and other temperature steam treated banana trunk waste particleboard. The dimensional stability of steam pre-treated banana trunk waste particleboard was found to be improved due to a reduction in thickness swelling and water absorption properties. The physical and mechanical property of steam pre-treated banana trunk waste particleboard was found to be comparable with the standard particleboard properties issued by the Japanese Industrial Standards (JIS) A 5908:2003. The finding of this study shows that the banana trunk waste has potential to be used as raw material for the manufacture of binderless particleboard, which can be used in green buildings.